Hak Asasi Manusia: Perspektif Islam - Mahmudi, Zaenul (el Harakah: Jurnal Budaya Islam, 2000)
Along with the advancement of human civilization, conversations concerning human rights issues will not subside in time, because the parameters of a civilized nation is if a civilization has been able to put people in proportion, can "humanize" humans. Human rights are of the utmost importance, because human beings can be real human beings if their basic rights are fulfilled and guaranteed after fulfilling their obligations. The denial of human rights implies the denial of human existence which Allah says is used as khalifah fil al ardh. In order to support the universality of Islam and the position of Islam as rahmatan Iil Alamin, the Koran regulates all aspects of human life in all its deeds, both the deeds of the heart and the physical deeds, whether in relation to the faith, ethics, and practical both governing relationships between individuals and individuals, with society, individuals with the state, individuals with the environment, and individuals with their God. Seiring dengan kemajuan peradaban manusia, perbincangan yang menyangkut permasalahan hak asasi manusia tidak akan surut tertelan zaman, karena parameter suatu bangsa yang beradab adalah apabila suatu peradaban telah dapat mendudukkan manusia secara proporsional, bisa "memanusiakan" manusia. Hak asasi manusia menjadi sangat penting, karena manusia bisa menjadi manusia yang sebenamya apabila hak asasinya telah terpenuhi dan terjamin setelah menunaikan kewajibannya. Pengingkaran terhadap hak asasi manusia berarti pengingkaran terhadap eksistensi manusia yang kata Allah dijadikan sebagai khalifah fil al ardh. Dalam rangka mendukung universalitas Islam dan posisi Islam sebagai rahmatan Iil Alamin, Quran mengatur semua aspek kehidupan manusia dalam segala perbuatannya, baik perbuatan hati maupun perbuatan fisik, baik yang berkenaan dengan itikad, etika, maupun praktis, baik yang mengatur hubungan antar individu dengan individu, dengan masyarakat, individu dengan negara, individu dengan lingkungan, maupun individu dengan Tuhannya.